Hydrologic processes of vegetated swales in controlling urban stormwater - Rujner, Hendrik (Luleå tekniska universitet, Arkitektur och vatten, 2024)
Vegetated swales are an integral component of Green Stormwater Infrastructure (GSI), designed to manage urban stormwater at its source by reducing volumes and peaks, retaining water within the urban landscape, and providing high-capacity runoff pathways. They facilitate the integration of vegetation-based stormwater solutions with traditional grey infrastructure, creating synergies and enhancing urban drainage. In light of contemporary urban drainage challenges, swales are now assigned multiple functions beyond stormwater conveyance, necessitating enhanced predictability and reduced uncertainties in their hydrologic performance. This thesis investigates the hydrologic functions of vegetated swales in controlling urban stormwater. Vegetated swales are shallow, vegetated channels that manage runoff through infiltration, conveyance, storage, dissipation, and filtration, leading to reduced runoff volumes and attenuated peak flows. The study aims to advance the understanding of swale functions by examining their hydrologic and hydraulic performance under varying conditions. Key objectives include exploring the relationship between hydraulic and hydrological factors and swale hydrographs, such as soil moisture dynamics and swale characteristics, representing swale processes and spatial variability, and evaluating long-term hydrological behavior concerning soil water content (SWC). The methodology involved field experiments and long-term monitoring at two swales in Luleå and a combined stormwater control measure (SCM) in Skellefteå, Northern Sweden. These swales, with differing topographies and vegetative covers, were subjected to controlled irrigation experiments to mimic runoff inflows. The combined SCM, consisting of a rocky slope, vegetated slope, and vegetated collector swale arranged in series, was monitored to assess hydrologic parameters and responses based on natural rainfall inflows. Data collection included rainfall events, inflow and outflow hydrographs, soil infiltration, and SWC using Time Domain ...